2015
DOI: 10.5039/agraria.v10i2a4075
|View full text |Cite
|
Sign up to set email alerts
|

Resistência à mancha-bacteriana e características agronômicas de linhas recombinadas de Capsicum annuum L.

Abstract: RESUMOO objetivo deste trabalho foi avaliar a reação à mancha-bacteriana (RMB) e o desempenho agronômico de 18 linhas recombinadas, provenientes do cruzamento entre um pimentão suscetível (UENF 1421) e uma pimenta resistente (UENF 1381). Para RMB, seis plantas de cada genótipo foram conduzidas em casa de vegetação, e inoculadas com suspensão bacteriana na concentração de 10 5 ufc mL -1 . A avaliação foi realizada por dois métodos: a escala de notas, variando entre 1 (resistente) e 5 (suscetível) e pela área ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In RILs 1, 2, and 6 and the cultivar 'Casca Dura Ikeda', capsaicin was absent (Table 2). These data agree with those obtained by Moreira (2008). Capsaicin, an alkaloid that confers pungency in the fruits of some Capsicum spp, is produced in the placenta and released when the fruit is physically damaged (Moreira et al, 2006).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In RILs 1, 2, and 6 and the cultivar 'Casca Dura Ikeda', capsaicin was absent (Table 2). These data agree with those obtained by Moreira (2008). Capsaicin, an alkaloid that confers pungency in the fruits of some Capsicum spp, is produced in the placenta and released when the fruit is physically damaged (Moreira et al, 2006).…”
Section: Resultssupporting
confidence: 89%
“…RILs evaluated in this study were originally derived from crosses between accessions UENF 1381 and UENF 1421, and thus far, the selection made in the advanced generations of this bi-parental cross are considered to have several agronomic attributes and resistance to BS (Moreira, 2008;Riva-Souza et al, 2009;Moreira et al, 2009Moreira et al, , 2010. Thus, the presence of different phenotypic expressions in the descriptors evaluated shows the variability of the RILs, even those aiming for selection for specific traits, as well as the efficiency of these descriptors in the differentiation of RILs.…”
Section: Resultsmentioning
confidence: 99%
“…From the scoring scale, the results showed that all P 1 parent plants reached an incidence of 100%, i.e., all plants were susceptible ( Figure 4A). These findings corroborate those reported in preceding studies such as Moreira et al (2013aMoreira et al ( , 2015. Moreover, P 2 had its resistance confirmed ( Figure 4B), as already observed by Moreira et al (2010Moreira et al ( , 2013b and Pimenta et al (2016).…”
Section: Resultssupporting
confidence: 93%
“…It confirms this genotype resistance since the smaller the affected area, the more resistant is a genotype (Table 1). Riva-Souza et al (2009) and Moreira et al (2015), evaluating plants at the same time, also confirmed resistance by lower means for the same resistant parent, which were 15.67 and 15.5, respectively. Likewise, Demosthenes and Bentes (2011), evaluating resistance to bacterial wilt in of Capsicum accessions, reported plants with lower AUDPC, being classified as resistant.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation